A comparative analysis between montessori and Al-Ghazali’s perspectives on child education = Analisis komparatif terhadap prinsip-prinsip al-Ghazali dan montessori dalam pendidikan kanak-kanak - Abdullah, Norillah; Abdul Razak, Mohd Abbas (IIUM Press, International Islamic University Malaysia, 2018)
Childhood education goes with a lot of innocence, searching and exploring the environment that surrounds the young learners. The amount of energy and inquisitiveness displayed by children at this tender age is a marble to many parents and teachers alike. This small-scale research represents a sincere attempt to contrastively analyze Montessori and Al-Ghazali’s ideas on child education. The ideas of the two scholars, one from the West and the other from the East, till these days have great significance to their respective communities. In a way, this study should be seen as an initiative undertaken in the absence of a study discussing the differences and commonalities found in the ideas of the two scholars pertaining to child education. By employing the textual analysis method and using Montessori’s principles of child education as the framework, the researchers conducted a comparative analysis. In the course of analyzing the data, the researchers had identified six emerging themes in the ideas of Montessori and Al-Ghazali. The findings have also indicated that the principles of these two prominent scholars either intersect with each other or stand in total isolation. ********************************************************* Pendidikan kanak-kanak berlakumalalui proses pencariandan penerokaanterhadap persekitaran mereka. Keceriaan dan sifat ingin tahu yang dipamerkan oleh kanak-kanak dalam proses tersebut amatlah penting bagi para ibubapa dan guru Pandangan-pandangan Montessori dan Al-Ghazali tentang pendidikan kanak-kanak telah meninggalkan kesan yang amat penting dalam komuniti Barat dan Timur hingga ke hari ini. Kajian ini dilakukanuntuk membandingkan pandangan kedua-dua cendekiawan ini tentang pendidikan kanak-kanak. Secara tidak langsung, ia boleh dilihat sebagai usaha untuk mengisi kekurangan dalam bidang kajian. Kajian ini menggunakan kaedah analisa tekstual dan prinsip pendidikan kanak-kanak Montessori sebagai rangka kajian. Daripada kajian ini, terdapat enam tema yang boleh digarapkan daripadapandangan kedua-dua cendekiawanyang didapati secara bersilang atau terpisah di antara satu sama lain.